2013
DOI: 10.1371/journal.pone.0078083
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NgBR Is Highly Associated with Estrogen Receptor Alpha and Survivin in Breast Cancer

Abstract: NgBR is a type I receptor with a single transmembrane domain and was identified as a specific receptor for Nogo-B. Our recent findings demonstrated that NgBR binds farnesylated Ras and recruits Ras to the plasma membrane, which is a critical step required for the activation of Ras signaling in human breast cancer cells and tumorigenesis. Here, we first use immunohistochemistry and real-time PCR approaches to examine the expression patterns of Nogo-B and NgBR in both normal and breast tumor tissues. Then, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 40 publications
0
72
0
Order By: Relevance
“…NgBR mRNA levels are increased in ductal adenocarcinoma and nonsmall cell lung carcinoma specimens (84,85). Clearly, regulation of glycosylation influences cell growth because the loss of ALG genes required for protein N-glycosylation triggers cell cycle arrest in yeast (86).…”
Section: Genetic Validation Of Two-component Ngbr/hcit Complex In Humansmentioning
confidence: 99%
“…NgBR mRNA levels are increased in ductal adenocarcinoma and nonsmall cell lung carcinoma specimens (84,85). Clearly, regulation of glycosylation influences cell growth because the loss of ALG genes required for protein N-glycosylation triggers cell cycle arrest in yeast (86).…”
Section: Genetic Validation Of Two-component Ngbr/hcit Complex In Humansmentioning
confidence: 99%
“…In addition, studies showed that Nogo-B can be a promising parameter for lower malignancy in breast or lung carcinomas (Wang et al 2013;Pula et al 2014). Nogo-B expression indicates neuronal regeneration in the central nervous system, and was identical to that of the apoptosis-inducing gene in human carcinomas (Li et al 2001).…”
Section: Macroscopic Findingmentioning
confidence: 99%
“…Our preliminary results show that overexpression of amino-terminal domain of Nogo-B (AmNogo-B) does not cause any significant effects on tumor cell growth and cell survival (data not shown). Knockdown of NgBR also does not significantly affect the growth and survival of MCF-7 cells under basal growth condition [28]. The detailed roles of NgBR in breast cancer really need further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic knockdown of either NogoB or NgBR by antisense morpholino abolished intersomitic vessel formation during developmental angiogenesis, and those defects can be rescued by constitutively activated Akt [27]. Our recent studies further demonstrated that NgBR is highly expressed in human breast invasive ductal carcinoma [28]. However, the exact roles of NgBR in the progression of cancer are still unclear.…”
Section: Introductionmentioning
confidence: 99%